Clinical and echocardiography predictors of response to inhaled nitric oxide in hypoxemic term and near‐term neonates. Issue 5 (12th January 2021) - Bischoff, Adrianne R.; Giesinger, Regan E.; Neary, Elaine; Weisz, Dany E.; Belik, Jaques; McNamara, Patrick J.
Abstract: Approximately 40% of hypoxemic term/near‐term neonates are nonresponders to inhaled nitric oxide (iNO). Phenotypic characterization of patients less likely to respond may improve diagnostic precision and therapeutic decisions. We conducted a retrospective cohort study of neonates born ≥35 weeks gestation with hypoxemia who received iNO in the first 72 h of life and classified them into responders and nonresponders according to changes in the fraction of inspired oxygen, saturations and/or arterial partial pressure of oxygen after 1 h of administration. Comprehensive targeted neonatal echocardiography (TnECHO) data were collected when performed up to 6 h prior or 24 h after iNO initiation. Descriptive statistics, univariate analysis, and binary logistic regression were used to compare the groups. There were 183 patients included (63% responders) and TnECHO was performed in 54 infants. The presence of lung disease, and particularly meconium aspiration syndrome ( p  = .004), was associated with nonresponse to iNO. Nonresponders were characterized by a higher need for rescue high‐frequency ventilation ( p  < .001), longer duration of mechanical ventilation ( p  < .001), and need for oxygen support ( p  = .003). Pulmonary hypertension documented on TnECHO was present in 96.3% of the patients but there was no difference in frequency or severity of pulmonary hypertension, or rates of low cardiac output between the groups. Moderate‐to‐severe right ventricular systolic dysfunction ( p  > .05) and lower left ventricular strain ( p  < .05) were more likely in the nonresponder group. In summary, response to iNO is influenced by lung disease, choice of ventilation strategy, and perhaps underlying cardiovascular physiology. Prospective pre‐ and post‐iNO echocardiography data may provide novel physiologic insights.